Interdisciplinary Obstetric Simulation for Common Obstetric Emergencies. (October 2017) - Durst, Jennifer; Temming, Lorene; Gamboa, Christine; Tuuli, Methodius; Macones, George; Young, Omar
Abstract : BACKGROUND: Duty hour restrictions limit trainee exposure to obstetric emergencies. Additionally, nursing turnover creates an area of need for increased education for preparation for these emergencies. Simulation has been used to improve physician performance, communication, and medical documentation; however, whether these benefits extend to all providers is understudied. METHODS: We conducted a quasi-randomized prospective educational trial targeted toward L&D nurses with less than 2 years' experience and junior obstetric residents. Participants were exposed to a pretest examining their knowledge (multiple choice, yes/no, free text responses) and comfort level (measured utilizing the Likert scale) with three common obstetric emergencies: shoulder dystocia, emergency cesarean delivery, and eclampsia. Participants underwent a simulation of one of the scenarios, watched their video-taped performance, participated in a debrief and educational session, and then repeated the simulation. Participants were administered a posttest following the simulation. RESULTS: Eighteen L&D nurses and 17 obstetric residents participated. Examination of the pre- and posttest results revealed improvements in the comfort level with shoulder dystocia maneuvers ( P =.0178), communication during a shoulder dystocia ( P =.0339), medical management of an eclamptic seizure ( P =.0190), and knowledge of how to appropriately administer magnesium to an eclamptic patient without an IV ( P =.0047). DISCUSSION: Interdisciplinary collaboration through the use of obstetric simulation can be utilized to improve knowledge and comfort necessary for the management of obstetric emergencies for both obstetric residents and L&D nurses.